Sobre a identificação com os líderes: um estudo dos comportamentos competitivos e cooperativos no cotidiano escolar - Mazzante, Fernanda Pinheiro (2009)
This search is written as the theoretical basis of critical theory of society, especially those of Theodor Adorno, Herbert Marcuse and Max Horkheimer, is based also in the works of Freud, interpreted by frankfurtians. It was studied the competitive and cooperative behavior adopted by a group of 31 students the second year of high school in the southern zone of São Paulo, from the relationship of leadership and submission within the established peer group in the room class. The school leaders identification was made through the questionnaire allowed the measurement of trends in students' behavioral issues competition and cooperation. The observation made indicated the existence of two basic forms of leadership: narcissistic and non-narcissistic. The data indicated that a leader narcissistic behavior presents more focused on the competition, however, was not found in this study, a significant relation between narcissism and non-cooperative behavior trend. The results showed that the identification with the leaders produces behavioral trends directly related to the psychological profile that led to the present as a reference. The narcissistic leader raised in their leadership competitives behaviors and non-narcissistic cooperatives behaviors. The figure of the teacher has been fundamental with regard to the restriction of the activities geared towards students more aggression